If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 13 + -2t + 3t = -5 + -4 Combine like terms: -2t + 3t = 1t 13 + 1t = -5 + -4 Combine like terms: -5 + -4 = -9 13 + 1t = -9 Solving 13 + 1t = -9 Solving for variable 't'. Move all terms containing t to the left, all other terms to the right. Add '-13' to each side of the equation. 13 + -13 + 1t = -9 + -13 Combine like terms: 13 + -13 = 0 0 + 1t = -9 + -13 1t = -9 + -13 Combine like terms: -9 + -13 = -22 1t = -22 Divide each side by '1'. t = -22 Simplifying t = -22
| 6x-17=47+6x | | 2(5p-8)=-96 | | 5x-20+5x+4y=180 | | 2x+3=1x-7 | | 4b-8b=24 | | Y=X^3+15x^2+74x+120 | | y^2+45y-63=0 | | 1/2(6-a)=a | | 8x+17=-29+16x | | 8+-3=9 | | 3k-1= | | -6=5n+5+4 | | -3(-4x+5)=17 | | 15-4x=75 | | 4+8y=11y-17 | | 24-6x+2x=12 | | 5j= | | 12*1x-17=20 | | x+3(x-1)=13 | | 3x-5y=-4 | | 26=5(w+4)-8w | | 2+4b=2+2b | | 4x=15+1X | | 5x^2-41x+8= | | 5x-4=180 | | 13-1x*14=9 | | 5(w)=84 | | 50-23d-d^2=0 | | x-9+3x=-14 | | 1=2u+7 | | -5(2x+-10)=-35x+50+25x | | 1=7+2 |